The predictive effect of cultural orientations on Chinese gifted students’ growth mindsets - Jiang, Huifei (Frontiers in Education, 2025)
The study examined the predictive effect of cultural orientations on Chinese gifted students’ growth mindsets. This study encompassed 378 gifted students from universities in mainland China. Gifted students’ growth mindset beliefs and cultural orientations were assessed by using Dweck’s growth mindset inventory and Hofstede’s cultural value scale, respectively. Data analysis mainly leveraged Pearson correlation analysis and hierarchical multiple regression analysis to test the hypothesize role of gifted students’ cultural orientations in predicting their growth mindsets. Pearson correlation analysis was used to assess the bivariate correlation between growth mindset and cultural orientations. Subsequently, Hierarchical multiple regression analysis was conducted to test the predictive effects of cultural orientations on growth mindset beliefs of gifted students. The results revealed that the cultural dimensions of long-term orientation can positively predict gifted students’ growth mindset, but power distance and uncertainty avoidance negatively predict their growth mindsets. Collectivism (or individualism) and femininity (or masculinity) cannot predict growth mindsets. Theoretically, this study underscores the necessity of accounting for cultural contexts when applying the growth mindset framework. Practically, it highlights the need to incorporate cultural factors into growth mindset interventions targeted at gifted students.